BBF Deceleration Down‐Tail of X < −15 RE From MMS Observation. Issue 2 (3rd February 2020) - Zhang, L. Q.; Baumjohann, W.; Khotyaintsev, Yu. V.; Burch, James L.; Webster, J.; Wang, J. Y.; Wang, C.; Dai, L.; Zhang, C. Y.
Abstract: We report the direct observation on bursty bulk flow (BBF) deceleration down‐tail of X < −15 RE by MMS satellite. Two typical events are presented in the paper. In the first event on 05 June 2018, MMS1 is located at X ~ −16.1 RE and records four individual bursty flows (BFs). Each burst flow has distinctly lower velocity than the preceding one. Accompanying with the decelerated BFs, the Bz/Bx continuously increases/decreases. Simultaneous Vx‐decrease and Bz‐increase are in coincidence with the scenario of the local BBF deceleration and formation of the magnetic pileup region. In the second event on 03 July 2017, MMS stays in the neutral sheet of X ~ −24.5 RE, and encounters similar BBF deceleration process. For both events, the decelerated BF series exhibit prominent medium‐energy ion component (2–10 KeV). Analyses show enhanced parallel current (J// ) and Kinetic Alfvénic wave (KAW) emitting during the BF intervals. The strength of the emitted KAW has a clear tendency to decay with the BBF decreasing. Power spectra density analysis confirms the substantial Joule dissipation during the BBF deceleration, both J// and J⊥ . Combined analyses support BBF dissipation via Joule heating as well as KAW emitting. Finally, we propose a possible mechanism on the BBF deceleration, i.e., "collision" with the tailward flow. Key Points: Bursty bulk flow (BBF) is decelerated down‐tail of X < −15 RE and forms the localized magnetic pileup region Field‐aligned current and Kinetic Alfvénic wave (KAW) emitting are substantially enhanced within the decelerating bursty flow series The decelerated BBF contains prominent medium‐energy ion component (2–10 keV)